2022
DOI: 10.1101/2022.04.29.22274496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vestibular contribution to path integration deficits in ‘at-genetic-risk’ for Alzheimer’s disease

Abstract: Path integration changes may precede a clinical presentation of Alzheimer disease by several years. Studies to date have focused on how grid cell changes affect path integration in preclinical AD. However, vestibular input is also critical for intact path integration. Here, we developed a naturalistic vestibular task that requires individuals to manually point an iPad device in the direction of their starting point following rotational movement, without any visual cues. Vestibular features were derived from th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Likewise, path integration errors exhibited high sensitivity and specificity in differentiating between positive and negative biomarker status in the MCI group (AUC = .90), outperforming other 'gold-standard' cognitive tests of global cognition, episodic memory, and putative measures of allocentric navigation. Further analyses revealed that path integration errors in MCI due to AD were driven primarily by increased angular noise when encoding the rotation between legs of the outbound path as well as when estimating the correct heading of the inbound path (Castenaro et al, 2023; see also Chrastil & Warren, 2017;Coughlan et al, 2023;Newton et al, 2023).…”
Section: Figure 2 the Triangle Completion Task Is A Common Assessment...mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, path integration errors exhibited high sensitivity and specificity in differentiating between positive and negative biomarker status in the MCI group (AUC = .90), outperforming other 'gold-standard' cognitive tests of global cognition, episodic memory, and putative measures of allocentric navigation. Further analyses revealed that path integration errors in MCI due to AD were driven primarily by increased angular noise when encoding the rotation between legs of the outbound path as well as when estimating the correct heading of the inbound path (Castenaro et al, 2023; see also Chrastil & Warren, 2017;Coughlan et al, 2023;Newton et al, 2023).…”
Section: Figure 2 the Triangle Completion Task Is A Common Assessment...mentioning
confidence: 99%
“…Interestingly, the predictive efficacy of path integration tasks is most robust in the absence of external visual landmarks, suggesting that path integration errors associated with the earliest pathological changes in AD may emerge primarily from faulty or noisy vestibular inputs (Castenaro et al, 2023;Coughlan et al, 2023). A recent meta-analysis suggests that the predictive efficacy of spatial navigation to differentiate between relative AD risk status is most robust when using tasks that enable free ambulation during navigation with the full complement of body-based idiothetic cues (Plácido et al, 2022).…”
Section: Figure 2 the Triangle Completion Task Is A Common Assessment...mentioning
confidence: 99%
See 1 more Smart Citation